SITUATIONAL AND PSYCHOLOGICAL PROFILE OF DAIRY FARMERS OF KANNUR DISTRICT IN KERALA - P. Vidya; C. Manivnnan and N. K. Sudeepkumar (J. Vet. Animal Sc, 2009)
A study was carried out to know the situational and psychological characteristics of dairy farmers of Kannur district in Kerala. Sixty dairy farmers were selected as respondents for the study by proportionate random sampling technique amongst the member dairy farmers of four milk co-operative societies identified in Kannur block. The findings of the study revealed that majority of the respondents possessed small herd size, medium level of milk production (3.66 to 11.2 litres per day), medium contact with extension agency, innovation proneness, economic motivation and decision making behaviour with considerable yeasr of experience in dairy farming. Their mass media exposure was medium to high and most of them were old aged with primary to secondary education